The perceived workload of first-line healthcare professionals during neonatal resuscitation - Hai-Bo Huang; Kui Sang; Ming Zhou; Lin Yi; Jiang-Qin Liu; Chuan-Zhong Yang; Brenda H.Y. Law; Georg M. Schmölzer; Po-Yin Cheung (Resuscitation Plus)
Background: Neonatal resuscitation is stressful for healthcare professionals as measured using the National Aeronautics and Space Administration-Task Load Index (NASA-TLX). Little is known regarding the perceived workload and associated factors among healthcare professionals including medical doctors (MDs) and nurses/midwives who have differences in training and experiences. We aimed to characterize and compare the perceived workload between MDs and nurses/midwives who provided neonatal resuscitation. Methods: In a prospectively designed, cellphone-based surveillance, perceived workload and stress of MDs and nurses/midwives during neonatal resuscitation was evaluated using a modified multi-dimensional NASA-TLX survey in three tertiary Neonatal Intensive Care Units in China. The NASA-TLX data on mental, physical, temporal demand, performance, effort, and frustration were independently rated by participants and collated to a composite score of all dimensions. Demographics of participants and deliveries were also collected for statistical analyses using univariate comparison and multiple linear regression. Results: From 410 valid surveys (187 (46%) MDs; 223 (54%) nurses/midwives), significant differences were noted between MDs and nurses/midwives including working years and dimensional and overall NASA-TLX scores. While MDs had lower overall NASA-TLX scores than nurses, their scores were inversely related with simulation-based training. More team members presence during resuscitation was associated with higher NASA-TLX scores. Other independent factors associated with NASA-TLX scores included gestational age, Apgar score at 1 min, year of practice for MDs and all resuscitation questions asked by nurses/midwives. Conclusions: MDs and nurses/midwives attending deliveries had different perceptions in workload and stress which could be lowered from simulation-based training in neonatal resuscitation.